2019
DOI: 10.1101/gad.327494.119
|View full text |Cite
|
Sign up to set email alerts
|

Protein aggregation mediates stoichiometry of protein complexes in aneuploid cells

Abstract: Aneuploidy, a condition characterized by chromosome gains and losses, causes reduced fitness and numerous cellular stresses, including increased protein aggregation. Here, we identify protein complex stoichiometry imbalances as a major cause of protein aggregation in aneuploid cells. Subunits of protein complexes encoded on excess chromosomes aggregate in aneuploid cells, which is suppressed when expression of other subunits is coordinately altered. We further show that excess subunits are either degraded or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 43 publications
8
95
0
Order By: Relevance
“…By contrast, autologous over-expression of proteins, such as for instance Pub1, is linked to other effects. In this case toxicity arises for i) the imbalanced complex stoichiometry caused by over-expression and ii) the subsequent formation of assemblies 85 in which Pub1 and its interactors become unavailable to perform their normal physiological functions. Thus, aberrant condensation creates the conditions for inappropriate molecular sequestration (loss of function) 86 and occurrence of undesired reactions (gain of function) 87 .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, autologous over-expression of proteins, such as for instance Pub1, is linked to other effects. In this case toxicity arises for i) the imbalanced complex stoichiometry caused by over-expression and ii) the subsequent formation of assemblies 85 in which Pub1 and its interactors become unavailable to perform their normal physiological functions. Thus, aberrant condensation creates the conditions for inappropriate molecular sequestration (loss of function) 86 and occurrence of undesired reactions (gain of function) 87 .…”
Section: Discussionmentioning
confidence: 99%
“…Unpaired OST complex partners might be deregulated in their function or cause harm to other proteins by exposing otherwise masked hydrophobic patches in the lumen or charges in the TM region . Severe protein complex stoichiometry imbalance is observed in aneuploid cells leading to induction of stress response pathways (Brennan et al, 2019;Oromendia et al, 2012). Since aneuploidy is a hallmark of cancer cells, the need for RHBDL4-mediated removal of surplus complex subunits may explain why the RHBDL4/Rhbdd1 gene is transcriptional upregulated in various forms of tumors (Song et al, 2015;Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a dynamic protein homeostasis (proteostasis) network ensures that damaged cellular proteins are efficiently removed and that protein complexes assemble in the correct stoichiometry . When not corrected by the protein degradation machinery, imbalance of protein stoichiometry generates a major fitness defect by leading to toxic protein species and protein aggregation (Brennan et al, 2019). The endoplasmic reticulum (ER) is the major site for protein synthesis, maturation and quality control for all proteins within the secretory pathway (Ellgaard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In aneuploid cancer it has been shown that messenger RNA (mRNA) levels generally correlate well with an increased DNA copy number (gene dosage) but these changes are not reflected at the protein level for several genes (Stingele et al, 2012) . Indeed, gene dosage compensation in cancer cells has been recently (Brennan et al, 2019) demonstrated at the protein level, whereby protein aggregation mediates the stoichiometry of protein complexes in aneuploid cells. In that study they show that excess subunits are either degraded or aggregated and that protein aggregation is nearly as effective as protein degradation at lowering the level of functional proteins (Brennan et al, 2019) .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, gene dosage compensation in cancer cells has been recently (Brennan et al, 2019) demonstrated at the protein level, whereby protein aggregation mediates the stoichiometry of protein complexes in aneuploid cells. In that study they show that excess subunits are either degraded or aggregated and that protein aggregation is nearly as effective as protein degradation at lowering the level of functional proteins (Brennan et al, 2019) .…”
Section: Introductionmentioning
confidence: 99%